2023
DOI: 10.1021/acsomega.2c07226
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MWCNT-Based Nanofluids for Photovoltaic/Thermal Cooling through Preparation Parameters

Abstract: Multiwalled carbon nanotubes (MWCNTs) were employed as added particles for nanofluids in this practical investigation. To identify the most appropriate nanofluid for cooling PVT systems that are functional in the extreme summer environment of Baghdad, the parameters of base fluid, surfactant, and sonication time used for mixing were examined. Water was chosen as the base fluid instead of other potential candidates such as ethylene glycol (EG), propylene glycol (PG), and heat transfer oil (HTO). Thermal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 92 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…The quantification of the relationship between CNT concentration and thermal conductivity enhancement allows for the optimization of CNT concentration for specific applications. Chaichan et al [89] showed that CNT nanofluid thermal conductivity increased with increased MWCNT concentration; see Figure 6a. The results are also in congruence with simulation results reported earlier [90]; see Figure 6b.…”
Section: Cnt Concentrationmentioning
confidence: 95%
“…The quantification of the relationship between CNT concentration and thermal conductivity enhancement allows for the optimization of CNT concentration for specific applications. Chaichan et al [89] showed that CNT nanofluid thermal conductivity increased with increased MWCNT concentration; see Figure 6a. The results are also in congruence with simulation results reported earlier [90]; see Figure 6b.…”
Section: Cnt Concentrationmentioning
confidence: 95%